Diatoms of Acadia National Park, Maine, USA, with a detailed account on taxonomy and morphology of several remarkable species - Veselá, Jana (Jihočeská univerzita, 2014)
This thesis was focused on studying diatoms (Bacillariophyceae) from Acadia National Park, Maine, USA. First, the park is introduced and the preliminary study of freshwater algae, including diatoms, is presented. Extraordinary species richness of algae was discovered, especially in the group of diatoms, which is documented by a complete list of 674 diatom taxa in 92 genera encountered in the freshwater and brackish habitats within the park. Of those a considerable number of species unfortunately remained unidentified, as they did not conform to any described taxon in the available scientific literature. Therefore, several of those unnamed taxa were studied in close detail using light and scanning electron microscopes, exhaustive literature and herbaria search, and yielded description of three new species from genus Eunotia, and rediscovery of two rare and almost forgotten Surirella species.
Diatoms of Acadia National Park, Maine, USA, with a detailed account on taxonomy and morphology of several remarkable species
Keywords: diatom; Acadia National Park; North America; taxonomy; Eunotia; Surirella; diatom; Acadia National Park; North America; taxonomy; Eunotia; Surirella